2008
DOI: 10.2135/cropsci2007.06.0340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Between‐Row and Within‐Row Spacing on Alfalfa Seed Yields

Abstract: Proper between‐row and within‐row spacing is essential for optimizing alfalfa seed yields and stand longevity. Using three alfalfa (Medicago sativa L.) cultivars (WL232HQ, Derby, and Algonquin), we conducted a field study from 2004 to 2007 to evaluate the effects of three between‐row spacing treatments (60, 80, and 100 cm) and four within‐row spacing treatments (15, 30, 45, and 60 cm) on seed yield, seed yield components, plant height, basal stem diameter, and lodging. Our hypothesis was that the intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
(32 reference statements)
6
20
0
1
Order By: Relevance
“…Alfalfa is one of the most important forage crops worldwide because of its good forage quality, high forage yield in a wide range of environments, and high adaptability to different climatic conditions (Dordas, 2006;Berg et al, 2007;Zhang et al, 2008;Turan et al, 2009). Alfalfa is grown mainly for forage production while seed yield is secondary (Iannucci et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa is one of the most important forage crops worldwide because of its good forage quality, high forage yield in a wide range of environments, and high adaptability to different climatic conditions (Dordas, 2006;Berg et al, 2007;Zhang et al, 2008;Turan et al, 2009). Alfalfa is grown mainly for forage production while seed yield is secondary (Iannucci et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The desired balance of grass and alfalfa in a native grassland may be achieved partially by choosing a robust, competitive cultivar and a seeding density that confers a stable arrangement of competing species (Chamblee and Collins, 1988). Planting seeds at different seeding rates or row spacings are methods of manipulating plant density (Zhang et al, 2008). Studies on alfalfa row spacings ranging from 15 to 100 cm have shown that wider spacing favored greater persistence than narrow row spacing (Askarian and Hampton, 1993; Groya and Sheaffer, 1981; Zhang et al, 2008).…”
mentioning
confidence: 99%
“…Planting seeds at different seeding rates or row spacings are methods of manipulating plant density (Zhang et al, 2008). Studies on alfalfa row spacings ranging from 15 to 100 cm have shown that wider spacing favored greater persistence than narrow row spacing (Askarian and Hampton, 1993; Groya and Sheaffer, 1981; Zhang et al, 2008). However, a majority of the trials were conducted under irrigation.…”
mentioning
confidence: 99%
“…The present study findings are in agreement with the result of these experiments that Ca supply could significantly increase pods per raceme (Table 4). In addition, some researchers reported that seeds per pod was a steady relatively component in lots of crops (Idris, 2008;Zhang et al, 2008). Similarly, in this experiment, Ca application had not significant effect on seeds per pod.…”
Section: Discussionmentioning
confidence: 43%